2022
DOI: 10.3390/app12094693
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Initial Conditions on Wind Characteristics at a Bridge Middle Span in a U-Shaped Valley by CFD and AHP

Abstract: The wind parameter distribution law at a bridge midspan in a U-shaped valley has important influence on the wind strength of this bridges. In this paper, the wind characteristics were researched by computational fluid dynamics (CFD). The surface roughness, the inlet wind speed, the wind speed profile, and the oncoming wind direction were selected as the initial conditions; the wind speed, the wind attack angle, and the wind azimuth angle were set as wind parameters; and the effect of the four initial condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In addition to temperature, the initial condition of chlorine concentration distribution in the water tank is another factor that can the predictions of residual chlorine. Although CFD simulation undoubtedly relies on the initial condition, 35 initializing a non-uniform condition is a significant challenge for CFD modeling, especially when it is unobservable. The impact of the initial condition in the study was demonstrated by the larger uncertainty in chlorine concentration variation during the first 400 min for UGT, which was caused by the unrealistic initial condition of uniformly-distributed chlorine concentration.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to temperature, the initial condition of chlorine concentration distribution in the water tank is another factor that can the predictions of residual chlorine. Although CFD simulation undoubtedly relies on the initial condition, 35 initializing a non-uniform condition is a significant challenge for CFD modeling, especially when it is unobservable. The impact of the initial condition in the study was demonstrated by the larger uncertainty in chlorine concentration variation during the first 400 min for UGT, which was caused by the unrealistic initial condition of uniformly-distributed chlorine concentration.…”
Section: Resultsmentioning
confidence: 99%